2015
DOI: 10.1016/j.ijfatigue.2015.06.005
|View full text |Cite
|
Sign up to set email alerts
|

Thermo-mechanical and superimposed high-cycle fatigue interactions in compacted graphite iron

Abstract: The eect of adding a superimposed high-frequent strain load, denoted as a high-cycle fatigue strain component, upon a strain-controlled thermomechanical fatigue test has been studied on a compacted graphite iron EN-GJV-400 for dierent thermo-mechanical fatigue cycles and high-cycle fatigue strain ranges. It is demonstrated that the successive application of an high-cycle fatigue load has a consistent eect on the fatigue life, namely the existence of a constant high-cycle fatigue strain range threshold below wh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
36
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 24 publications
(37 citation statements)
references
References 15 publications
1
36
0
Order By: Relevance
“…Regarding TMF testing with superimposed HCF, only a handful of experimental studies have been carried out on cast irons including the work of this thesis [37][38][39][44][45][46]. Nevertheless, it has been reported that there is an existence of a consistent HCF strain range, below which the fatigue life is unaffected by the superimposed HCF load, for LGI, CGI and SGI [39,44,46].…”
Section: Crack Initiation and Propagation During Cyclic Loadingmentioning
confidence: 99%
See 2 more Smart Citations
“…Regarding TMF testing with superimposed HCF, only a handful of experimental studies have been carried out on cast irons including the work of this thesis [37][38][39][44][45][46]. Nevertheless, it has been reported that there is an existence of a consistent HCF strain range, below which the fatigue life is unaffected by the superimposed HCF load, for LGI, CGI and SGI [39,44,46].…”
Section: Crack Initiation and Propagation During Cyclic Loadingmentioning
confidence: 99%
“…Nevertheless, it has been reported that there is an existence of a consistent HCF strain range, below which the fatigue life is unaffected by the superimposed HCF load, for LGI, CGI and SGI [39,44,46]. Regarding the fatigue crack mechanisms, extensive studies have only been conducted on SGI.…”
Section: Crack Initiation and Propagation During Cyclic Loadingmentioning
confidence: 99%
See 1 more Smart Citation
“…However, the repetition of start-up and shutdown of engines can cause high mechanical loading and may lead to localized crack at the engine blocks and heads as a result of thermo-mechanical fatigue [1,2]. From this aspect, researchers have found that Compacted Graphite Iron (CGI) is the best candidate in replacing CI.…”
Section: Introductionmentioning
confidence: 99%
“…Similarly, the model presented by Norman et al [87] (Paper II) was also based on Paris' law, Equation 5, combined with Equation 4 to account for a superimposed HCF load. In contrast to previous models, the crack length was interpreted as an average of a large number of microcracks and the point of failure as the instant when the average microcrack length gets in the same order as the average distance between microcracks.…”
Section: Fatigue Life Estimationmentioning
confidence: 99%